Leaf carbohydrates during flowering and early growth stages of fruitlets in 'Ponkan' mandarin tree - Moreira, Rodrigo Amato; da Cruz, Maria do Céu Monteiro; Fagundes, Miriã Cristina Pereira; Pantoja, Lílian de Araújo; dos Santos, Alexandre Soares (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the levels of carbohydrates in the leaves of 'Ponkan' mandarin tree (Citrus reticulata), during full flowering and early growth stages of fruitlets, and to identify the best time to perform chemical thinning. The experiment was carried out for two production years (2009/2010 and 2010/2011), with four sampling times of leaves: 0, 30, 60, and 90 days after full flowering. A randomized complete block design, split‑plotted in time with four replicates and four plants per plot, was used. To determine the use of carbohydrates by plants, the contents of soluble sugars, reducing sugars, and starch in the dry matter of leaves were evaluated. At the same leaf sampling times, fruitlet size was also determined. Leaf contents of soluble carbohydrates increase and the ones of starch decrease between 35 and 50 days after full flowering. At the end of the fruit setting phase, from the 50th day after full flowering, the contents of soluble sugars in leaves reduce. The best time to perform chemical thinning in 'Ponkan' mandarin tree is soon after the physiological drop phase, when the fruitlets reach around 18 mm, at the 50th day after full flowering.